The effect of biological control on the population dynamics of Pontederia crassipes Mart. (Pontederiaceae) and Salvinia minima Baker (Salviniales: Salviniaceae) - Chikodza, Tressia (Rhodes University, Faculty of Science, Botany Department)
Pontederia crassipes is widely regarded as the most damaging floating aquatic weed in terms of its invasive traits, and its impact on aquatic ecosystems. Biological control using host-specific natural enemies is widely used for its control, with the most recent agent released being a planthopper, Megamelus scutellaris, in South Africa and the USA. In South Africa, inundative releases of M. scutellaris have been shown to control the weed even at eutrophic, and high elevation cold sites, such as Hartbeespoort Dam, arguably Africa's most hypertrophic impoundment. However, subsequent to the control of P. crassipes on Hartbeespoort Dam, in 2021, a secondary invader, Salvinia minima, dominated the water system. Salvinia minima is only known from a handful sites near Hartbeespoort Dam and there is currently no approved biocontrol agent for it. The population dynamics of P. crassipes and S. minima at the Dam were overall interchanging due to insect feeding on M. scutellaris reducing P. crassipes populations thus allowing S. minima to become dominant. Intense feeding from M. scutellaris resulted in the reduction of P. crassipes populations. During late autumn and winter, remaining P. crassipes plants experienced frost damage from cold temperatures. The decrease in P. crassipes allowed S. minima to successfully invade, potentially as the result of less competition from P. crassipes, and therefore available resources, such as space, nutrients, and light. However, as spring approached, P. crassipes regenerated from its seed bank, and S. minima populations diminished. The changes in dominance were observed in 2021 and 2022 but in 2023, this trend was not evident as S. minima did not dominate as in previous years. This thesis investigated the combination of competition and herbivory by M. scutellaris on the vigour of P. crassipes and S. minima to understand the dynamics of these two highly invasive species. Competitive abilities of P. crassipes and S. minima were determined using an inverse linear model with plant weight as the yield variable. In the absence of herbivory, P. crassipes, was 4 times more competitive than S. minima, but as competitive when exposed to M. scutellaris feeding. Salvinia minima was 1.2 times as aggressive as P. crassipes in the absence of herbivory, but 2.6 times as competitive when M. scutellaris was established on P. crassipes. In the presence of herbivory on P. crassipes, interspecific competition coefficients from P. crassipes on S. minima were no longer statistically significant. These results indicate that the competitive ability of P. crassipes was reduced through herbivory when grown with S. minima, explaining the temporal dominance between the two species at Hartbeespoort Dam. Some studies have reported that P. crassipes releases allelochemicals as a competitive strategy to algae and phytoplankton. Previously identified allelochemicals include N-phenyl-1-naphthylamine, N-phenyl-2-naphthylamine and linoleic acid. This thesis investigated the presence or absence of key chemical compounds released by P. crassipes during allelopathy with microbes and phytoplankton to determine its potential to inhibit S. minima growth. Methanol extracts from P. crassipes roots, leaves, and field samples underwent LC-ESI-MS/MS analysis, creating a molecular network to match chemical profiles. Of the investigated compounds, N-phenyl-1-naphthylamine and N-phenyl-2-naphthylamine were absent in P. crassipes and field samples, while linoleic acid was consistently found. Its presence suggests its potential defensive role against S. minima. Future research should explore allelochemical production in the presence of S. minima and algae to confirm if S. minima elicits an allelochemical response by P. crassipes, or whether the methods used here were insufficient to detect allelochemical production. Understanding whether P. crassipes employs allelochemicals, especially in the presence of S. minima, could shed light on its competitive advantage beyond its invasive nature at the Dam.
Keywords: Pontederia crassipes; Salvinia minima; Pontederiaceae Biological control -- South Africa; Salviniaceae Biological control -- South Africa; Population dynamics; Secondary invasion